The psychopharmacology of herbal medicine : plant drugs that alter mind, brain, and behavior - Spinella, Marcello (MIT Press, 2001)
Virtually all cultures consume drugs from psychoactive plants. Caffeine, for example, is probably the most common stimulant in the world, and many modern medicines, such as morphine and codeine, are derived from plant sources. In these cases, scientific research has revealed the composition of the plants and how they interact with the nervous system. There are also many herbal medications with reputed therapeutic value that have not yet gained acceptance into mainstream medicine, partly because there has not been enough research to support their usefulness. Instead they are regarded as "alternative medicines." This is an active research area, however, and many current studies are focusing on identifying the active components, pharmacological properties, physiological effects, and clinical efficacy of herbal medicines. This book compiles and integrates the most up-to-date information on the major psychoactive herbal medicines -- that is, herbal medicines that alter mind, brain, and behavior. It focuses particularly on the effects on various areas of cognition, including attention, learning, and memory. The book covers all major classes of psychoactive drugs, including stimulants, cognitive enhancers, sedatives and anxiolytics, psychotherapeutic herbs, analgesics and anesthetic plants, hallucinogens, and cannabis. - Publisher